Teachers’ perceptions of social support in the co-planning of multidisciplinary technology education - Aarnio, Hanna Emilia (Design and Technology Education: An International Journal, 2021)
In Finland, technology education is a multidisciplinary field where team teaching serves as a basis for the integration of technology across different school subjects. However, Finnish teacher education does not adequately prepare the student teachers for multidisciplinary technology education, and the professional competency is often gained through voluntary participation in professional development courses. The resulting individual differences in teachers’ technology education competency hinder their ability to plan such educational offerings together. While previous studies have identified multidisciplinary team teaching as a way of balancing out individual differences in teachers’ professional competency, the ability to leverage it depends on the availability of social support. Previous studies have examined the effect of social support in teachers’ professional well-being, but further research on its role in organising multidisciplinary technology education is needed. This study explores what kind of social support is involved in the co-planning of multidisciplinary technology education. Eleven experienced in-service teachers representing different school subjects participated in interviews carried out in 2019–2020. The data were analysed by applying the principles of qualitative content analysis. The findings revealed that instrumental support in the form of new ideas, tools, and methods was emphasised in the teachers’ experiences. The perceived needs for more social support were mainly related to making joint decisions during the co-planning process. The findings indicate that co-planning in multidisciplinary teams increases the versatility of possible implementations of technology education. However, leveraging multidisciplinary team teaching would require more support for pedagogical leadership.